The Analysis of the Content Component Effectiveness for Teacher Training in the Magistracy Conditions of the Technical Institution in Higher Education - Vira Vykhrushch; Anatoliy Vykhrushch (Pedagogical Discourse, 2018)
The article deals with the empirical study of the problem of the teacher preparing in higher educational establishment in the conditions of the master preparation, ensuring its general pedagogical preparation of the masters, made the analysis of the content component of the strategies for preparing graduate students for teaching activities in higher educational establishments of different profiles, the formation of the future teacher professional competence under the influence of the content part in the pedagogical conditions of technical higher educational establishments, the diagnostical examination was made and the realistic state of masters preparing in higher educational establishment of different profiles to their teaching activity in the context of the reflexive pedagogic. Proceeding from the fact that the objective aim of training a teacher in the conditions of the magistracy of institutions of higher education of different fields is to ensure its reflexive orientation, the formation of a future specialist implies its realization on an andragogical basis, taking into account the peculiarities of its content of the research and pedagogical universities educational environment; appropriate approaches to the content component of the technical higher educational institution teacher training have been formulated. For the realization of the tasks in the context of research the content of the general teacher training system in the conditions of the magistracy, taking into account the profile of the institution of higher education, was analyzed. The problems of content of the teacher’s general training preparation in the conditions of the magistracy in the higher educational technical institutions at context of reflexive pedagogy was singled out.On the basis of research, the problems of improving the teacher training system content in the conditions of the master’s degree in pedagogical and technical institutions have been identified. The reliability of the results of the invastigation has been confirmed by the criterion of the reliability of the differences between the mean values of the Student’s t-criterion for independent samples.